Female Characters in the Play Dhruvaswāminī: ध्रुवस्वामिनी नाटक मे नारी चरित्र - Chaturvedi, Santosh Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In this play, Prasad Ji supports the cause of the exploited woman. He envisions woman as a life-giving, nourishing stream flowing through the beautiful plane of life. On one hand, inspired by the woman’s benevolent nature, the playwright, on the authority of religious scriptures, grants women the right to liberation (moksha) and restores their social dignity through the provision of remarriage. On the other hand, through the words of “Koma,” he raises the demand for eternal womanhood. In essence, while Prasad Ji wishes to see women established and respected in society, he also seeks, for the welfare of the world, to uphold in women the values of sacrifice, service, love, and compassion. Abstract in Hindi Language: इस नाटक में प्रसाद जी ने निर्यातित स्त्री के पक्ष का समर्थन किया है, उन्होंने जीवन के सुंदर समतल में स्त्री को पीयूष स्रोत- सी बहने के लिए कहा है। एक ओर नारी की कल्याण भावना से प्रेरित नाटककार ने धर्म शास्त्र के साक्ष्य पर स्त्री को मोक्ष का अधिकार दिलाया है और पुनर्विवाह के विधान द्वारा उसकी सामाजिक प्रतिष्ठा की है। वहीं दूसरी ओर उन्होंने ‘ कोमा ‘ के शब्दों में शाश्वत स्त्रीत्व की मांग उठाई है। वस्तुतः प्रसाद जी जहां नारी को समाज में प्रतिष्ठित एवं सम्मानित देखना चाहते हैं वहां विश्व कल्याण के लिए नारी में त्याग, सेवा, प्रेम एवं करुणा की भी प्रतिष्ठा चाहते हैं। Keywords: नारी सुलभ गुण, नारी की सामाजिक प्रतिष्ठा, नारी में त्याग और समर्पण, विरोध की भावना